ANALYSING YOUTHS’ PERCEPTIONS ON GREEN TECHNOLOGY POLICY AND AWARENESS ON ENVIRONMENT PROTECTION USING A TWO-STEP LEAST SQUARES METHOD - Sarimah, Surianshah; Audrey, Liwan (2021)
This study analysing the model of youths’ perceptions on green technology policy and their awareness level on environment protection. This study aims to address potential endogeneity in the model by introducing a few instruments in the two-step least squares model. A total of 300 Sabahan youths respondents had participated in this study. The finding of this study shows that there is an endogeneity issue in the baseline model with statistically significant post-estimation tests. After addressing the potential bias in the baseline model, this study finds that the positive effects between high youths’ perceptions on green technology policy efficacy and high awareness on environment protection become five times higher. It suggests for the government and policymakers to embark on youths involvement in spreading positive attitudes towards environmental protection as they are the future catalyst of Sabah particularly and Malaysia in general